What kind of consciousness is minimal? - Kotchoubey, Boris; Vogel, Dominik; Lang, Simone; Müller, Friedemann (Brain injury, 2014)
Primary objective: A comparison between unitary and non-unitary views on minimal consciousness.Research design: First, unitary (all-or-none) and non-unitary (gradual or continuous) models of consciousness are defined as they have been developed in both philosophy and neurophysiology. Then, the implications of these ideas to the notion the minimally conscious state (MCS) are discussed.Methods and procedures: Review and analysis of theoretical conceptions and empirical data.Main outcome and results: Both kinds of models are compatible with the actual definitions of MCS. Although unitary views may seem to contradict the description of the MCS in ‘Neurology’ 2002, the apparent contradiction can easily be solved. Most recent data, particularly those obtained using fMRI and concerning learning, emotional responsiveness and pain and suffering, speak for non-unitary models.Conclusions: Most evidence speaks for non-unitary models of minimal consciousness. If these models are correct, patients with MCS may have, in addition to temporal fluctuations, a lower level of consciousness compared with fully conscious individuals. A still lower level could characterize patients diagnosed as unresponsive wakefulness syndrome (UWS). From this point of view, therefore, the difference between UWS and MCS is gradual rather than qualitative. However, due to methodological limitations of the available studies, the evidence for non-unitary models cannot be regarded as definite.